Impacts of traditional livestock farming on threatened sheldgeese (Chloephaga spp.) in Patagonia - Natalia A. Cossa (Resilience Alliance, 2020)
Migratory sheldgeese (continental Upland Goose Chloephaga picta, Ashy-headed Goose C. poliocephala, and continental Ruddy-headed Goose C. rubidiceps) are endemic birds of southern South America. They are currently threatened by illegal hunting, overgrazing, and invasive predators. Because their breeding area is intensely grazed by sheep and cows, we studied the interaction of sheldgeese flocks and breeding pairs with livestock in the Tierra del Fuego and Santa Cruz provinces in Patagonia, Argentina. We conducted road-based surveys of sheldgeese flocks and breeding pairs from spring 2013 to summer 2016 to explore sheldgeese behavior. In addition, we monitored Upland Goose nests using camera traps and estimated nest daily survival rates in nests unprotected and protected from livestock with an electric fence. Sheldgeese flocks and breeding pairs were more frequently sighted alone than associated with livestock. Also, when sheldgeese foraged alongside livestock, there were fewer individuals resting and these allocated more time to forage than in the absence of livestock. We did not observe lower individual vigilance in sheldgeese flocks sharing foraging patches with livestock. Nests protected by electric fences had higher daily survival rates than unprotected ones. Our results indicate that one important conservation action should be to identify areas that concentrate a great number of breeding pairs of sheldgeese, and protect them from livestock, mainly during the peak of the reproductive season.